Optimizing ACL Reconstruction: A Comparative Analysis of Clinical Outcomes between Double Bioabsorbable Interference Screws and Hybrid Fixation Techniques - Tommy Widjaya; Otman Siregar; Husnul Fuad Albat (Universitas Muhammadiyah Palu, 2026)
Background: Anterior Cruciate Ligament (ACL) rupture is a prevalent injury necessitating reconstruction to restore stability and prevent osteoarthritis. The choice of graft fixation—specifically between aperture fixation using interference screws and suspensory fixation using buttons—remains a subject of debate regarding their impact on functional recovery. Objective: This study aims to compare the clinical functional outcomes of patients undergoing ACL reconstruction using the Double Bioabsorbable Interference Screw (DBIS) technique versus a combination of Femoral Button and Tibial Bioabsorbable Screw (Hybrid technique), utilizing the International Knee Documentation Committee (IKDC) score. Methods: An observational analytic study with a case-control design was conducted at RSU Haji Medan. The study involved 50 patients divided equally into two groups (n=25 for DBIS, n=25 for Hybrid). Inclusion criteria were primary isolated ACL reconstruction, age 18-59 years, and at least 6 months post-operation. Functional outcomes were assessed using the IKDC score pre-operatively and at 1, 3, and 8 months post-operatively. Data were analyzed using independent t-tests. Results: The DBIS group had a significantly younger mean age (41.48 ± 4.03 years) compared to the Hybrid group (43.92 ± 2.97 years, p=0.019). Gender distribution was balanced (p=0.777). IKDC scores showed significant improvement over time in both groups. However, there were no statistically significant differences in IKDC scores between the DBIS and Hybrid groups at any time point: Pre-operative (41.04 vs 40.84, p=0.881), Month 1 (50.08 vs 50.24, p=0.875), Month 3 (67.12 vs 67.48, p=0.767), and Month 8 (87.72 vs 88.48, p=0.448). Conclusion: Both DBIS and Hybrid fixation techniques result in comparable and favorable functional outcomes at 8 months post-surgery. The choice of fixation may depend on surgeon preference and cost rather than short-term clinical superiority.